Progesterone as a tocolytic agent for preterm labor: a systematic review. Issue 6 (December 2016) - Navathe, Reshama; Berghella, Vincenzo
Abstract : Purpose of review: Tocolytic agents have been used for over 60 years in the fight against preterm labor, which ultimately can lead to preterm birth. Currently, clinicians can choose from a variety of drug classes to achieve the primary goal of delaying delivery by 48 h, thereby allowing time for administration of corticosteroids for fetal lung maturity, and if appropriate, starting magnesium sulfate for fetal neuroprotection. However, there are currently no known therapies to maintain the tocolytic effect beyond those initial 48 h. Recent findings: Progesterone, which has been used in the prevention of preterm birth for over 10 years, has long been known to have the effect of uterine quiescence. It was first studied as a tocolytic agent in the 1960s. In the last several years, more studies have been done that suggest a potential use for maintenance tocolysis after the successful arrest of preterm labor. Although the studies are conflicting, the meta-analyses on progesterone show some promise in different outcomes of delayed delivery, reduced incidence of preterm birth, and reduced neonatal morbidity. Summary: Progesterone is currently the most promising agent for maintenance tocolysis. Although further trials are certainly needed, this is an exciting advancement in the realm of tocolysis.